Legal writing style - Gidi, Antonio, 1968-; Weihofen, Henry, 1904-1993 (USA : West Academic Publishimg, 2018)
"Legal Writing Style promotes the art of good writing by teaching students and practitioners the tools to make their prose clear, precise, simple, and forceful. With examples of what works and what doesn't, this short but comprehensive treatise provides an invaluable resource for recasting writing for maximum impact and ultimate success"--Publisher website
Introduction -- Precision -- Conciseness -- Simplicity -- Clarity -- Forcefulness -- Organization -- A touch of eloquence -- Conclusion -- Further readings
Includes bibliographical references and index